Intimacy as political imagination: the folk of Feliciano Centurión’s artworks (Palíndromo, 2025)
On a postmodern scene, where different identities cross each other, it is noticeable the defilement between areas usually seen as opposites. In this context, this research aimed to analyze the place of the Paraguayan Feliciano Centurión’s art work between dichotomies as cult or folk, hegemonic or subaltern, modern or traditional. Thus, designations as Arte Light, Arte Rosa and Arte Guarango were analyzed, since they are results of the Centurión’s bond with the Centro Cultural Ricardo Rojas, which was essential for the artistic scenario in Buenos Aires in the 1990s. This study also aspired to consider the symbolical and political aspects under the artist’s employment of the quotidian and of the textile, where he explores intimacy, femininity, homoeroticism and some Paraguayan textile traditions, as the Ñanduti and the Ao Po’i. Furthermore, this research was based on a bibliography related to the history of art and to the cultural studies, focused on the Latin American context and on the diverse meanings of folk. As a result, based on studies of hybridism, this study indicates Centurión as an amphibious artist, since he strains the canon while residing in multiples categories.
Keywords: Contemporary art; Textile Art; Paraguayan craftsmanship; Folk culture; Feliciano Centurión